Ireland : 2007 Article IV Consultation; Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2007)
This 2007 Article IV Consultation highlights that economic performance of Ireland remains strong, supported by sound policies. The growth rate of real GNP per capita continues to be one of the highest among advanced economies and the unemployment rate one of the lowest. However, in recent years, economic growth became more reliant on house building, and competitiveness eroded. Rapidly rising housing prices were accompanied by surging bank credit to property-related sectors and strong wage growth. The banking system continues to perform well, but rapid credit growth has led to vulnerabilities.